PROBLEMS OF DEVELOPMENT OF HOUSING CONSTRUCTION IN THE REPUBLIC OF DAGHESTAN AT THE PRESENT STAGE - M. G. Azaev; M. M. Osmanov; G. N. Khadzhishalapov (Вестник Дагестанского государственного технического университета: Технические науки)
The article discusses the aims of public policy in a housing sphere and housing material well-being of population of Republic of Daghestan, the ways of their realization and problems of town-planning.